Penyelesaian Perkara Isbat Nikah di Pengadilan Agama Ambon - Mohamad Fauzan Kelian; Barzah Latupono; Sabri Fataruba (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Isbat Marriage is the government's effort to provide services to people who do not yet have a Marriage Certificate, so that they can re-establish their marriage. In the process there are still many couples who carry out unregistered marriages, namely unregistered marriages, so that their marriages are not recognized by the state and many still do not understand the law or the importance of registering marriages. The type of research in this research is normative research or legal literature research. The results of the study show that the reasons for applying for marriage certificates in the Ambon Religious Court are: (a) marriage certificates are submitted for making a marriage certificate; (b) complete the requirements for a child's birth certificate; (c) legally settle the divorce in the Court; (d) inheritance distribution; (e) the management of the pilgrimage; (f) filed due to loss of Marriage Certificate; and (g) obtain a retired second widow from the State Civil Apparatus (ASN). Meanwhile, with regard to the completion of applications for Isbat Nikah, the Ambon Religious Court will carry out in accordance with applicable regulations, starting from the registration stage at the Ambon Religious Court Office, paying the application fee down payment, awaiting summons from the court, attending trials and stipulations from the Ambon Religious Court regarding the application for Isbat Nikah.